A Magnetic Heterogeneous Biocatalyst Composed of Immobilized Laccase and 2, 2, 6, 6‐Tetramethylpiperidine‐1‐oxyl (TEMPO) for Green One‐Pot Cascade Synthesis of 2‐Substituted Benzimidazole and Benzoxazole Derivatives under Mild Reaction Conditions. Issue 18 (24th July 2018) - Mogharabi‐Manzari, Mehdi; Kiani, Mahshid; Aryanejad, Sima; Imanparast, Somaye; Amini, Mohsen; Faramarzi, Mohammad Ali
Abstract: The design of reusable high‐performance heterogeneous catalysts via the immobilization of chemical and biochemical species on magnetic nanoparticles increases the efficiency of catalytic systems by facilitating easy, fast, and clean separation processes. Laccase and 4‐amino‐2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl were separately immobilized on amine functionalized iron (II, III) oxide nanoparticles with covalent bonding using glutaraldehyde as a coupling reagent. The prepared catalyst was used to synthesize 12 benzoxazole and benzimidazole derivatives. The one‐pot, two‐step enzymatic aerobic oxidation reaction included the condensation of in situ‐ produced salicylaldehyde derivatives with aromatic amines, followed by an enzymatic dehydrogenation process. Optimal reaction conditions consisted of a citrate buffer (10 mM, pH 4.5) at 40 °C for an incubation time of 10 h and a heterogeneous catalyst containing immobilized laccase (80 mg, 100 U) and immobilized 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO) (40 mg, 2 mol%). The catalyst retained more than 85% of its initial activity after 10 runs. In addition to the potential for reuse without significant losses in performance, eco‐friendly attributes of this catalytic system include its high catalytic activity and the ease with which it can be recovered from the reaction mixture using an external magnet. Abstract :